Analisis Berfikir Kritis Siswa yang Bergaya Kognitif Reflektif dan Implusif pada Pembelajaran Biologi melalui Model Problem Base Learning (PBL) dengan Media Puzzle - Nikmah, Iik Nurliatun; Cintamulya, Imas (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Biology lesson demands in the national curriculum are expected to be able to think critically. In addition, other aspects that must be considered in the learning of the cognitive style of students. Therefore, it is necessary to conduct research that aims to describe the critical thinking ability of cognitive and implusive cognitive-style students in Biology learning through Problem Based Learning (PBL) model with Puzzle media. The subjects of this study consisted of 24 students of class VII G SMP Negeri 2 Tuban consisting of 12 students reflective cognitive style and 12 students cognitive style implusif. Data collection techniques in this research are Matching Familiar Figures Test (MFFT) developed by warli (2010) to find out students 'cognitive style and students' critical thinking test that refer to Ennis (1985) indicator. Further data on students' critical thinking ability with reflective and implusive cognitive style were analyzed using non parametric statistic using Mean Withney test. Based on the results of data analysis shows there are differences in the way students think critically between the cognitive-style reflective and implusive. Cognitive-style students are reflective in critical thinking higher than students with cognitive-style impulses. So it can be concluded that students with cognitive-style reflective critical thinking skills are better than cognitive-style students are implusive in Biology lesson through Problem Based Learning (PBL) learning model using Media Puzzle.